Urgensi Bimbingan Karier di SD/MI dalam Optimalisasi Tugas Perkembangan Peserta Didik - - Hidayat (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: One of the orientations in career Counseling and Guidance in Elementary School/Islamic Elementary School is helping the students attain certain attitude consciousness in making a choice and face any demand possibilities to choose between career and study. If the students make the wrong decision in choosing their career, they will come up ultimately with unwanted effects on their whole live satisfaction. Therefore, the right decision to choose between study or career becomes an important matter to the life of students as a human. Due to the importance of study/career problems in human being, making right decisions needs to be well-prepared since the children is at the elementary school in order to help them plan their future by giving them an ongoing education program and guidance. Nowadays, a counselor has no structural position in elementary school/Islamic elementary schools. Therefore, the position elementary school teachers’ is very important to play their role and carried the responsibilities to understanding the students and help students’ development task optimum.